Proximate analysis of fibres of grain sorghum, pearl millet and sesame residues and their fractions in Gadarif State, Sudan - Hamed, Asma H. M; Elimam, Mohmed E. (Gezira Journal of Agricultural Science, 2014)
Proximate analysis and fibres were determined in different fractions of sorghum stover [ Sorghum bicolor (L.) Moench.] (Arfaa gadamac variety), sesame straw ( Sesamum indicum L. ) and millet straw [ Pennisetum typhoides (Burm.)] with roots or without roots in Gadarif State, Sudan, in 2007. The plants were divided into upper, middle and lower parts and leaves. There were great variations in the composition of the straws and their fractions and they had low crude protein (CP) and high fibre content. Sorghum stover had the highest CP, ash and nitrogen free extract (NFE) and the lowest crude fibres (CF) and modified acid detergent fibres (MADF) among the crop residues. Millet straw had the lowest ether extract (EE) and NFE and the highest neutral detergent fibres (NDF) and MADF. Crude fibre was not significantly (P>0.05) different in millet and sesame straws. Leaves had the highest CP and lowest fibre content. Crop residues nutritive value declined from the top to the bottom of the  plants.      تم تحديد التحليل التقريبي والألياف المختلفة في الأجزاء المختلفة من تبن الذرة الرفيعة           ( صنف أرفع قدمك) وتبن السمسم وتبن الدخن بجذور او بدون جذور ، ولاية القضارف ، السودان. قسمت النباتات الى أجزاء عليا ، وـوسطى وسفلي وأوراق كاملة. وجدت اختلافات كبيرة في تركيب الأتبان واجزائها وكانت منخفضة البروتين الخام ومرتفعة الألياف. كان لتبن الذرة أعلى البروتين الخام والرماد والجزء الخالي من النتروجين وأقل الألياف الخام والألياف الذائبة في الحامض المعدلة بين أتبان المحاصيل. وكان لتبن الدخن أقل الدهون والجزء الخالي من النتروجين وأعلى الألياف الذائبة في المنظف والألياف الذائبة في الحامض المعدلة. تقاربت الألياف الخام  لتبني الدخن والسمسم ولم تختلف معنويا. الأوراق بها أعلى البروتين الخام وأقل الألياف. انخفضت القيمة الغذائية للأتبان من أعلى إلى أسفل.